Simulation of Flow and Heat Transfer of Nanofluid in an Eccentric Annulus with Multicomponent Lattice Boltzmann Method - Afsaneh Rostamzadeh; Ebrahim Goshatsbi Rad; Khosrow Jafarpur (Journal of Applied Fluid Mechanics, 2016)
In the present study, Lattice Boltzmann method is employed to investigate a two dimensional mixed convection heat transfer of Al2O3-water nanofluid in a horizontal annulus between a cold outer cylinder and the hot, rotating inner cylinder. To do so, the double lattice Boltzmann equation is utilized for the base fluid and the nanoparticles to describe the dynamic as well as the thermal behavior of nanofluid. Moreover, different forces such as Brownian, drag and gravity acting on the nanoparticles are taken into consideration. Calculations have been performed for Rayleigh number ranging from 103 to 2×104, Reynolds number from 5 to 120, vertical and horizontal eccentricity from -0.75 to 0.75 with volume fraction of nanoparticles from 0 to 0.1. The current computational results reveal that by adding nanoparticles, the mean Nusselt number for Ra <104 increases as Rayleigh number increases while in the case of Ra >104, it decreases. Also, with Re>80, the mean Nusselt number increases with increasing Reynolds number; although for low Reynolds number this rising trend is not observed. Besides, when the inner cylinder moves vertically upward from the center, the addition of nanoparticles increases Nusselt number relative to the base fluid.